2019
DOI: 10.3390/ijerph16122082
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sources of Salt in Low- and Middle-Income Countries: A Systematic Literature Review

Abstract: Rapid urbanization in low- and middle-income countries (LMICs) is transforming dietary patterns from reliance on traditional staples to increased consumption of energy-dense foods high in saturated fats, trans fats, sugars, and salt. A systematic literature review was conducted to determine major food sources of salt in LMICs that could be targeted in strategies to lower population salt intake. Articles were sourced using Medline, Web of Science, Scopus, and grey literature. Inclusion criteria were: reported d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 74 publications
2
14
0
1
Order By: Relevance
“…The results only show that any estimate provided for South America is larger than the result for the Caribbean; this is consistent with the findings by Powel and colleagues [7]. Different dietary sources could potentially explain the differences [30]; for example, meat and bakery seem to be relevant sodium sources in low-and middle-income countries [30] and we could argue that these, particularly meat, are more often consumed in South America. Gender and age distributions in the selected reports were largely similar across the countries, which may imply that these variables do not greatly explain the results.…”
Section: Results In Contextsupporting
confidence: 86%
“…The results only show that any estimate provided for South America is larger than the result for the Caribbean; this is consistent with the findings by Powel and colleagues [7]. Different dietary sources could potentially explain the differences [30]; for example, meat and bakery seem to be relevant sodium sources in low-and middle-income countries [30] and we could argue that these, particularly meat, are more often consumed in South America. Gender and age distributions in the selected reports were largely similar across the countries, which may imply that these variables do not greatly explain the results.…”
Section: Results In Contextsupporting
confidence: 86%
“…Further, Ghana's national salt iodization programme, along with accompanying major public health campaigns on iodine consumption [47][48][49][50] may partially be responsible for an increase in discretionary salt intake. However, lack of information on sources of salt provided from discretionary and non-discretionary Despite the current study not including a dietary assessment component, a recent systematic review of dietary sources of salt in LMICs identified that bread, meat and meat products, bakery products, instant noodles, salted preserved foods, milk and dairy products, and condiments were major sources thereof [51]. In some LMICs, bread alone may contain as much as 1.36 g salt per 100 g bread [52].…”
Section: Discussionmentioning
confidence: 88%
“…Such innovation has been directed towards the manufacture of productions that are more health-beneficial, and two different strategies have gradually been developed. The first strategy addresses the reduction of unhealthy compounds and ingredients, such as additives, fat, and salt [6,7]. The second is directed to enhance the nutritional contents of food, by adding compounds with health benefits, such as natural antioxidants like spices, omega 3 fatty acids, probiotics, etc.…”
Section: Introductionmentioning
confidence: 99%